Controlling through-space and through-bond intramolecular charge transfer in bridged D–D′–A TADF emitters. Issue 28 (30th June 2021) - Miranda-Salinas, Hector; Hung, Yi-Tzu; Chen, Yi-Sheng; Luo, Dian; Kao, Hao-Che; Chang, Chih-Hao; Wong, Ken-Tsung; Monkman, Andrew
Abstract : Donor–donor′–acceptor molecules where the donor′ bridges the donor and acceptor have different possible interaction pathways for charge transfer. Abstract : Donor–donor′–acceptor molecules where the donor′ bridges the donor and acceptor have different possible interaction pathways for charge transfer. Here we study a series of donor–donor′–acceptor molecules, having the same acceptor and donor′ but different donors, and donor′–phenyl spacer–acceptor to change the spatial separation and overlap between potential through-space donor–acceptor charge transfer (CT) in competition with donor′–acceptor through-bond CT. We determine that the charge transfer driving force plays a large role in dictating which charge transfer channel is favoured. Strong donors and acceptors with large driving force favour through-space CT. We also find that solid state host packing plays an important role, with small molecule hosts that pack tightly, distorting the guest molecules, reducing D–A separation to stabilise the through-space CT state over the through-bond state. Only the through-space CT states give fast reverse intersystem crossing and efficient TADF. These results give the first insight into the photophysics of through-space CT compared to through-bond states on the same molecule.